Follow-Up of Children With Autism Spectrum Disorder 1 Year After Early Behavioral Intervention. Issue 4 (July 2019) - Rivard, Mélina; Morin, Marjorie; Mello, Catherine; Terroux, Amélie; Mercier, Céline
The effectiveness of early intensive behavioral intervention (EIBI) for children with autism spectrum disorders (ASDs) has been demonstrated by many studies and meta-analyses. Although it is considered an exemplary practice in several countries, few studies have investigated the maintenance of gains made in EIBI over time. Thirty-two children were assessed at posttreatment and 1-year follow-up after they attended a low-to-moderate-intensity (10 to 20 hr per week) EIBI program delivered by a public rehabilitation center. Between baseline and posttreatment, children showed significant gains in most areas of intellectual functioning and a significant decrease of autism symptom severity, but no change in adaptive behavior. Gains in intellectual functioning were maintained over a 1-year period after treatment termination, but autism symptom severity had increased to approximately pretreatment levels during that interval. Considerable individual variability was noted in the evolution of outcomes.